Learning About/For Sustainability as Contested Space: Contemporary Characterizations of Adult Education in the Sustainable Agriculture Movement - Kim L. Niewolny; Nancy Grudens-Schuck; Arthur L. Wilson (Adult Education Research Conference, 2010)
We illustrate how various forms of adult education, and the interests they serve, help create spaces for learning in the sustainable agriculture movement as a neglected dimension of adult education research. Implications for further exploring the learning dimensions of social movements are discussed.